A Monte Carlo study of impact of scan position for cone beam CT on doses to organs and effective dose. (October 2018) - Abuhaimed, Abdullah; Martin, Colin J.
Abstract: For multi-detector CT scans, the region of the body irradiated is determined from the scan projection radiograph and is adjusted for each patient. However, for cone beam CT scans, standard field sizes are often used without any adjustment for patient size. Moreover, when cone beam CT is used with image guided radiation therapy, the scan position varies with each patient, based on the tumour position and clinical requirements. The aim of this study is to quantify the influence of the position of the scan isocentre on doses to organs and tissues within the patient, and derive values of effective dose that might be used in optimization of imaging protocols. A previously validated Monte Carlo model of a Varian kV on-board-imager system was used to assess organ and effective doses for the International Commission on Radiological Protection adult male and female reference phantoms. The scan isocentre was shifted along the z-axis of the phantoms in increments of 2.4 cm, while keeping the x and y axes fixed to assess variations in dose. The phantoms were divided into four regions, namely head and neck, thorax, abdomen, and pelvis. Each region was scanned using the protocol with scan parameters applied in the clinic. The position of the scan isocentre plays a major role in determining the organ doses and effective dose for all regions studied. Nevertheless, values for average effective dose derived at the centre of a region of interest would be suitable for planning treatment regimens and making adjustments to scan protocols. If conversion coefficients based on measurements made at centre of an area of interest were used to evaluate organ doses for individuals, these could lead to significant over/underestimation. The impact of changes in scan position should be taken into consideration when deriving doses to the organs of a patient. Highlights: Variations of organ doses with position of CBCT iscoentre were significant. An over/underestimation can be caused by generic conversion coefficients. Influence of the scan iscoentre should be taken into consideration. Conversion coefficients that account for this influence can provide a solution. Variations in average effective doses were lower than those for organ doses.